2013
DOI: 10.5402/2013/392632
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Southern Ocean Surface Temperature Variability Using Long-Term Optimum Interpolation SST Data

Abstract: An attempt is made to understand the long-term variability of SST using NOAA optimum interpolation SST data for the period (1982–2011) in the Southern Ocean. This dataset has been used (i) to study the interannual variability in SST anomaly and (ii) to carry out regression analysis to compute linear trend in the annual averaged Southern Ocean SST. It is observed that summer season exhibits more variability than winter. Moreover, El Nino/La Nina events apparently play a critical role in the variability of South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In the Pacific, ice volume begins decreasing in 2009, after the disintegration of C19a and B15a. Regional and temporal differences in iceberg volume, and sound level reflect the local distribution and stability of the ice sheets, iceberg drift paths, and sea-surface temperature anomalies [e.g., Maheshwari et al, 2013]. Romanov et al [2014] found possible links between El Niño events and iceberg concentration in the east Pacific and in the west Atlantic sectors of Southern Ocean but the results were still inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…In the Pacific, ice volume begins decreasing in 2009, after the disintegration of C19a and B15a. Regional and temporal differences in iceberg volume, and sound level reflect the local distribution and stability of the ice sheets, iceberg drift paths, and sea-surface temperature anomalies [e.g., Maheshwari et al, 2013]. Romanov et al [2014] found possible links between El Niño events and iceberg concentration in the east Pacific and in the west Atlantic sectors of Southern Ocean but the results were still inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not estimate trends in the bloom start date and bloom end date, we can expect a similar pattern to the ones detected for date of Dia-Chla maximum since these indices are highly correlated ( Figure S1 in the supplement). These observations combined with recent studies on the trends in sea surface temperature [64] and sea ice cover [65] over the last three decades, suggest a link between these two variables and the diatom phenology. For example, in the region south of 60 • S and from 60 • E to 120 • E (Figure 7, grey star) the earlier date of Dia-Chla maximum and the increased Dia-Chla maximum coincide with the observed increase trend in SST and decrease in sea ice cover (earlier sea ice melt).…”
Section: Trendsmentioning
confidence: 93%
“…It is increasingly clear that the response of phytoplankton to multiple stressors acting concurrently cannot be obtained by superimposing their separate responses (Boyd and Brown, 2015;Zhu et al, 2016;Boyd et al, 2016;Luxem et al, 2017;Andrew et al, 2019;Strzepek et al, 2019;Trimborn et al, 2019;Boyd, 2019). Satellite observations in the Southern Ocean show complex patterns of environmental change; surface warming in much of the Northern zone contrasts with slight cooling trends over the last 40 years further south (Maheshwari et al, 2013;Kostov et al, 2016;Sallée, 2018); average sea ice concentration has decreased in the Amundsen Sea but increased in parts of the Weddell, Bellingshausen and Ross Seas (Vaughan et al, 2013;Zhang et al, 2018;Pinkerton, 2019;IPCC, 2019); irradiance at the sea-surface has increased north of the Subantarctic Front and generally reduced to the south over the last 20 years; over the same period, mixed-layer depths have likely shallowed in the Northern zone, and both deepened and shallowed in different parts of the Subantarctic and Antarctic zones (Leung et al, 2015;Pinkerton, 2019).…”
Section: Mixed-layer Primary Productionmentioning
confidence: 99%